Safety and immunogenicity of SCB-2019, an adjuvanted, recombinant SARS-CoV-2 trimeric S-protein subunit COVID-19 vaccine in healthy 12-17 year-old adolescents - Pio Lopez; Lulu Bravo; Erik Buntinx; Charissa Borja-Tabora; Hector Velasquez; Edith Johana Rodriquez; Camilo A. Rodriguez; Josefina Carlos; May Emmeline B. Montellano; Edison R. Alberto; Milagros Salvani-Bautista; Yung Huang; et al. (Taylor & Francis Group, 2023)
We previously demonstrated the efficacy of the COVID-19 vaccine candidate, SCB-2019, in adults in the SPECTRA phase 2/3 efficacy study. We extended the study to include 1278 healthy 12-17-year-old adolescents in Belgium, Colombia, and the Philippines who received either two doses of SCB-2019 or placebo 21 days apart, to assess immunogenicity as neutralizing antibodies against prototype SARS-CoV-2 and variants of concern, and safety and reactogenicity as solicited and unsolicited adverse events with a comparator group of young adults (18-25 years). In participants with no evidence of prior SARS-CoV-2 infection SCB-2019 immunogenicity in adolescents was non-inferior to that in young adults; respective geometric mean neutralizing titers (GMT) against prototype SARS-CoV-2 14 days after the second vaccination were 271 IU/mL (95% CI: 211-348) and 144 IU/mL (116-178). Most adolescents (1077, 84.3%) had serologic evidence of prior SAR-CoV-2 exposure at baseline; in these seropositive adolescents neutralizing GMTs increased from 173 IU/mL (135-122) to 982 IU/mL (881-1094) after the second dose. Neutralizing titers against Delta and Omicron BA SARS-CoV-2 variants were also increased, most notably in those with prior exposure. SCB-2019 vaccine was well tolerated with generally mild or moderate, transient solicited and unsolicited adverse events that were comparable in adolescent vaccine and placebo groups except for injection site pain - reported after 20% of SCB-2019 and 7.3% of placebo injections. SCB-2019 vaccine was highly immunogenic against SARS-CoV-2 prototype and variants in adolescents, especially in those with evidence of prior exposure, with comparable immunogenicity to young adults. Clinical trial registration: EudraCT 2020-004272-17; ClinicalTrials.gov NCT04672395.